Late Pleistocene plant macrofossils from the Gokarna Formation of the Kathmandu valley, central Nepal - Bhandari, S; Paudayal, KN; Momohara, A (Journal of Nepal Geological Society, 2008)
The Gokarna Formation, constituting the middle part of the sedimentary sequence of the Kathmandu valley comprises alternating layers of carbonaceous clay, silt, fine- to coarsegrained sand and gravel that were deposited at fluvio-deltaic and lacustrine environment. The organic rich layers of clay, silt, silty-sand and micaceous fine sand consists of abundant plant macro-fossils (fruits, seeds and leaves). Plant macrofossil assemblage from the Gokarna Formation (thickness 28.5 m, Dhapasi section) in the northern part of the valley consists of 48 taxa. Depending upon the available plant assemblages, six fossil zones, DS-I to DS-VI in ascending order, were established. The dominant fossil fruits and seeds from these horizons mainly consists of the herbaceous plants such as Boehmeria (>20%), Polygonum (>5%), Carex (>17%), shrubby plants such as Eurya (48%), Rubus (>25%), Euphorbia (10%) and Zizyphus (>2.5%). The tree plants such as Ficus (>10%), Pyracanta (>18%) and Carpinus (14%) are also present abundantly. The lower horizons (DS-I and DSII) were dominated by the herbs and shrubs whereas the upper horizons were dominated by shrubs and trees. The shifting of vegetation from herbs to shrubs and trees indicates a fluctuation of climatic system. This minor fluctuation might have been due to shifting of cold climate to warm climate during the deposition of the Gokarna Formation. Journal of Nepal Geological Society, 2007, Vol. 36 (Sp. Issue) p.8